2013
DOI: 10.1155/2013/976967
|View full text |Cite
|
Sign up to set email alerts
|

Palm Tocotrienol-Rich Fraction Improves Vascular Proatherosclerotic Changes in Hyperhomocysteinemic Rats

Abstract: This study investigated the effects of palm tocotrienol-rich fraction (TRF) on aortic proatherosclerotic changes in rats fed with a high methionine diet. Forty-two male Wistar rats were divided into six groups. The first group was the control (fed with a basal diet). Another five groups were fed with 1% methionine diet for 10 weeks. From week 6 onward, folate (8 mg/kg diet) or palm TRF (30, 60, and 150 mg/kg diets) was added into the diet of the last four rat groups, respectively. The high methionine diet rais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…Thus, incorporation of palm oil into poultry diets provides a natural dietary source of vitamin E and may improve antioxidative status of the body. A palm oil extract rich in tocotrienols has been shown to reduce high methionine diet-induced aortic oxidative stress (Norsidah, Asmadi, Azizi, Faizah, & Kamisah, 2013a) and heart oxidative stress in rats (Norsidah, Asmadi, Azizi, Faizah, & Kamisah, 2013b). Moreover, supplementation of tocotrienol-rich fraction of palm oil improved antioxidant levels and conferred protection against oxidative stress in healthy adults over 50 years of age (Chin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, incorporation of palm oil into poultry diets provides a natural dietary source of vitamin E and may improve antioxidative status of the body. A palm oil extract rich in tocotrienols has been shown to reduce high methionine diet-induced aortic oxidative stress (Norsidah, Asmadi, Azizi, Faizah, & Kamisah, 2013a) and heart oxidative stress in rats (Norsidah, Asmadi, Azizi, Faizah, & Kamisah, 2013b). Moreover, supplementation of tocotrienol-rich fraction of palm oil improved antioxidant levels and conferred protection against oxidative stress in healthy adults over 50 years of age (Chin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Another risk factor associated with CVD and stroke is hyperhomocysteinemia [92]. This condition may lead to endothelial cell damage and altered flexibility of vessels [92] by reducing the availability of plasma nitric oxide (NO) and promoting pro-atherosclerotic inflammatory mediators like vascular adhesion molecules as well as oxidative stress in aorta [93] and heart [94]. Additionally, hypercholesterolemia is also one of the risk factors for CVD.…”
Section: Effects Of Tocotrienol On Cardiovascular Diseasesmentioning
confidence: 99%
“…One study in humans yielded a neutral effect of tocopherol, rather than tocotrienol, on homocysteine levels (Breilmann et al, 2010). Although the effect observed here is minimal, due to the correlation of homocysteine to cardiovascular risk (Nygård et al, 1995), further studies should aim to confirm this finding and look at the possible mechanisms involved, if any.…”
Section: Tocotrienol-tocopherol and Vitamin C In Hypercholesterolaemimentioning
confidence: 59%
“…Even though many in-vitro studies have reported tocotrienol's beneficial effect on adhesion molecules expression (Ahn et al, 2007;Naito et al, 2005;Theriault et al, 2002), ours is the only study that evaluated its role in human. However, the homocysteine elevation seen with TTMF treatment when compared to the baseline is in disagreement with a study in animals, which have demonstrated a beneficial lowering of homocysteine with tocotrienol treatment (Norsidah et al, 2013). One study in humans yielded a neutral effect of tocopherol, rather than tocotrienol, on homocysteine levels (Breilmann et al, 2010).…”
Section: Tocotrienol-tocopherol and Vitamin C In Hypercholesterolaemimentioning
confidence: 90%